Burden of illness of dog-mediated rabies in India: A systematic review - Denny John; Abhishek Royal; Omesh Bharti (Elsevier, 2021)
Introduction: India accounts for 35% of global burden of rabies. This systematic review attempts to measure the burden of illness of dog bites and dog-mediated rabies in India. Methods: A systematic literature search was conducted on MEDLINE, EMBASE, Cochrane Central, PROQUEST, Sodhganga and Google Scholar. Two independent reviewers screened titles and abstracts and included full texts as per inclusion criteria. Critical appraisal of included studies was conducted using appropriate checklists. Data was extracted using standardized data extraction tools, analyzed and reported in narrative summary and tabular formats. Results: 35 studies were included for narrative synthesis after screening for inclusion criteria. The annual crude dog bite incidence was reported between 0.26% and 2.5% with stray dogs as main biting animal. The bites were mainly reported in males, between age group 10-40 years, individuals belonging to low socio-economic status and people working in fields. The annual economic and humanistic burden is estimated to be 2.85 million USD and 1.3 million DALYs respectively. Use of intradermal route of vaccination and equine rabies immunoglobulins has been reported to save cost and resources over use of intramuscular route of vaccination and human rabies immunoglobulins. Conclusion: The review highlighted the burden of disease at local, regional and national level. There has been dearth of studies reporting economic and humanistic burden at national level. Systematic review registration: PROSPERO ID: CRD42020213261.